Inhibition of Human Epidermal Growth Factor Receptor-2 (HER-2) from Pomelo (Citrus maxima) Flavonoid Compounds: an In Silico Approach - Mutiah, Roihatul; Dewi, Tanaya Jati Dharma; Suryadinata, Arief; Qonita, Kesimira (Indonesian Journal of Cancer Chemoprevention, 2021)
Citrus maxima or pomelo is a plant that has potential as an anticancer because it contains flavonoids. One of the targets of breast anticancer receptors is the HER-2 protein. This research aims to determine the anticancer activity, the toxicity of the compound, and the prediction of physicochemical properties of flavonoids contained in Citrus maxima through in silico approach. Flavonoid compounds were screened using SwissADME with Lipinski's rule of five, Torsion, TPSA, and P-Gp Non-Substrate. Compounds that passed the screening were carried out molecular docking to the HER-2 receptor (PDB ID: 3PP0) using the Molegro Virtual Docker (MVD). The HER-2 receptor (GDP ID: 3PP0) was declared valid because it had RMSD<2Å. The results showed that there were 11 flavonoid compounds that passed the screening and had a lower rerank score than the comparison compound Trastuzumab. Toxicity was predicted using the Protox II online tool and the results showed that the flavonoid compounds were in the safe limits, namely classes 5 and 3. Based on this research, it can be concluded that acacetin, diosmetin, honyucitrin, isosinensetin, nobiletin, sinensetin, and tangeretin can be candidates for breast cancer drugs based on natural ingredients.Keywords: breast cancer, Citrus maxima, HER-2, in silico.